Pastoral Persahabatan Lintas Agama di Indonesia - Janter Rano Baki (CV. Ulil Albab Corp, 2023)
The reality of inter-religious violence, especially experienced by adherents of Christianity and Islam in Indonesia, continues to occur and becomes a common struggle. This article aims to seek the role of the Churches against inter-religious violence in Indonesia. Using a literature study approach, I explored the reality of interfaith violence from a variety of Christian, Islamic, and social thought and produced a service approach for churches in Indonesia. The findings of this article contribute to the Churches, namely the Pastoral approach of Interfaith Friendship. This approach offers two alternative issues, namely cross-religious pastoral dialogue that is correlational and globally responsible, and centered on shared vocation and responsibility for human suffering and the ecological crisis. Through this approach, the Church reconciles the tenuous relations between Christians and Muslims in Indonesia and even builds synergies in alleviating human and ecological problems.